2021
DOI: 10.1101/2021.01.06.425465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and Functional Analyses Explain Pea KAI2 Receptor Diversity and Reveal Stereoselective Catalysis During Signal Perception

Abstract: The α/β hydrolase KARRIKIN INSENSITIVE-2 (KAI2) mediates the perception of smoke-derived butenolides (karrikins) and an elusive endogenous hormone (KAI2-ligand, KL) found in all land plants. It has been suggested that KAI2 gene duplication and sub-functionalization events play an adaptative role for diverse environments by altering the receptor responsiveness to specific KLs. These diversification occurrences are exemplified by the variable number of functional KAI2 receptors among different plant species. Leg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 101 publications
(235 reference statements)
0
17
0
Order By: Relevance
“…Previous literature on the nature of the covalent modification include mass spectrometry showing a D-ring bound to H247 9 , a crystal structure of a CLIM species 4 , reanalysis of the CLIM structure suggesting that the electron density fits will with an intact D-ring 13 , and a crystal structure showing a D-ring on the catalytic serine in KAI2, a homolog of D14 with the same catalytic triad 37 . While these all initially appear to be competing views, our simulations show that all of these covalent modifications are likely to be present in some quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature on the nature of the covalent modification include mass spectrometry showing a D-ring bound to H247 9 , a crystal structure of a CLIM species 4 , reanalysis of the CLIM structure suggesting that the electron density fits will with an intact D-ring 13 , and a crystal structure showing a D-ring on the catalytic serine in KAI2, a homolog of D14 with the same catalytic triad 37 . While these all initially appear to be competing views, our simulations show that all of these covalent modifications are likely to be present in some quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present the crystal structure of A. thaliana DLK2, which, as a major difference to its paralogs AtD14 and AtKAI2, features a significantly smaller substrate binding pocket. Previous structures of strigolactone receptors or KAI2 clade proteins have shown that not only the substitution of amino acids inside the substrate binding pocket determines its size or ligand specificity (Guercio et al, 2022; Toh et al, 2015) but that also interactions between residues located in different secondary structure elements can influence the volume and shape of the pocket. This has been observed in a hydrogen bond between helices αD1 and αD3 in hyposensitive to light proteins from Striga hermonthica (ShHTL) (Xu et al, 2018) and in a loop region between helices αE and αF in KAI2‐like proteins from Physcomitrium patens (Bürger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Neither structure shows the dramatic conformational change found in the homologous SL receptor DWARF14 (D14) when it is in a putatively active complex with MAX2/DWARF3 (D3) (Yao et al, 2016). Finally, the chemistry of KARs is incompatible with the ligand hydrolysis model proposed for PsKAI2B in pea (Pisum sativum) (Guercio et al, 2022), because KARs do not have a suitable leaving group and would likely re-close upon nucleophilic attack (Scaffidi et al, 2012). However, this last point may be moot if ligand hydrolysis is not essential for signal transduction by KAI2, as has been hypothesised for D14 (Seto et al, 2019).…”
Section: Kai2 Is Probably Not a Karrikin Receptormentioning
confidence: 92%
“…KAI2 proteins that are putatively KL-responsive can be activated by synthetic molecules with hydrolysable, 2 0 S-configured butenolide rings, such as GR24 ent-5DS (Waters et al, 2015b;Carbonnel et al, 2020b;Sun et al, 2020;Wang et al, 2020b;Yao et al, 2021). The KAI2 catalytic triad undergoes a similar modification with the cleaved butenolide ring as DWARF14 (D14) does during SL hydrolysis (Guercio et al, 2022). This suggests KL may have some structural similarity to SLs.…”
Section: Kai2 Is Probably Not a Karrikin Receptormentioning
confidence: 99%